Effect of progressive muscle relaxation on pain threshold and effectiveness of footballers` training - Jaworska, L.; Hawrylak, A.; Burzynski, B.; Szczepanska-Gieracha, J. (Human Movement, 2015)
Purpose. Relaxing in the athlete`s training process is underutilized. Relaxation techniques, however, should be taught from the very beginning of the footballer`s training career. The main aim of this study was to present the effect of progressive muscle relaxation on pressure pain threshold levels and the effectiveness of the footballer`s training. Methods. A sample of 32 football players participated in the therapeutic program consisting of 8 PMR sessions. Before and after applying a pressure therapy, the pain threshold in the lumbar region was measured by a dolorimeter and the Cooper test was carried out to determine the footballers` level of endurance. Results. PMR training did not increase significantly the pain threshold level in the experimental group (p > 0.05), but it increased significantly the distance covered in the Cooper test (p = 0.04). Analysis of the Spearman rank correlation was also carried out (p = 0.81). Conclusions. PMR does not lower pain perception threshold. PMR therapy increases the distance measured by the Cooper test. In order to determine the role of PMR in injury prevention, further research is necessary.